INFLUENCE THE CHANNEL PATH ON HYDRO-THERMAL PERFORMANCE IN SERPENTINE MINI- CHANNEL HEAT SINK - Hind M. Mohammed; Basim H. Abood (Journal of Engineering and Sustainable Development, 2022)
The current work aims to inspect the influence of formation flow on hydrothermal performance and the uniformity of base temperature in the serpentine mini channel heat sink. The study was conducted by changing the flow formation with the straight channel model [A] and the wavy channel model [B] and by changing the place of inlet and outlet by putting the entrance at the heat sink center and using water as the working fluid. To obtain the numerical results, a 3D (ANSYS Fluent program) is used. A comparison between the numerical findings in the current work and experimental results from the literature review is carried out. The comparison shows moral agreement between the numerical and experimental findings. Moreover, the outcomes display that flow configuration has a great influence on the distribution of temperature and pressure drop. Although the model with straight channels enhances the temperature uniformity and pressure drop. Additionally, the overall performance factor (OPF) for all new models under study is better than traditional model. The average OPF for model [A] is (1.43) and for model [B] is (1.26). In addition, model [A] is better as compared with model [B] by 11.89% due to the efficient OPF and the uniformity of temperature in the base.